2008
DOI: 10.1017/s0952523808080358
|View full text |Cite
|
Sign up to set email alerts
|

Changes in induced hues at low luminance and following dark adaptation suggest rod-cone interactions may differ for luminance increments and decrements

Abstract: Color contrast describes the influence of one color on the perception of colors in neighboring areas. This study addressed two issues: (1) the accurate representation of the color changes; (ii) the underlying visual mechanisms. Observers matched the hue that was induced in a neutral square when it was set in one of four standard colored surrounds: "red" (+L(-M) relative to neutral), "green" (-L(+M)), "purple" (+S), and "yellow" (-S). The standard and matching displays were viewed haploscopically. The standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…In addition to affecting the perceived hue, brightness, and saturation, rod activity can alter cone-mediated chromatic discrimination ( Stabell and Stabell, 1977 ; Nagy and Doyal, 1993 ; Knight et al, 1998 , 2001 ; Cao et al, 2008b ; Shepherd and Wyatt, 2008 ; Volbrecht et al, 2011 ). In comparison to measurements under photopic illumination, chromatic sensitivity measured under mesopic illuminations is differentially altered in the areas of the protan, deutan, and tritan confusion lines, with the greatest sensitivity loss near the tritan axis, but in general, the magnitude of the rod intrusion is small when measured with luminance contrast masking techniques ( Walkey et al, 2001 ).…”
Section: Rod Contributions To Mesopic Color Visionmentioning
confidence: 99%
“…In addition to affecting the perceived hue, brightness, and saturation, rod activity can alter cone-mediated chromatic discrimination ( Stabell and Stabell, 1977 ; Nagy and Doyal, 1993 ; Knight et al, 1998 , 2001 ; Cao et al, 2008b ; Shepherd and Wyatt, 2008 ; Volbrecht et al, 2011 ). In comparison to measurements under photopic illumination, chromatic sensitivity measured under mesopic illuminations is differentially altered in the areas of the protan, deutan, and tritan confusion lines, with the greatest sensitivity loss near the tritan axis, but in general, the magnitude of the rod intrusion is small when measured with luminance contrast masking techniques ( Walkey et al, 2001 ).…”
Section: Rod Contributions To Mesopic Color Visionmentioning
confidence: 99%
“…The background colours that were chosen for the present study were selected to differentially activate the cone opponent pathways early in the visual system (cardinal colour directions). Care was taken to ensure that the colours selected for the experiment were equally saturated (after Shepherd, 1997b;Shepherd and Wyatt;2008) and of equal measured luminance. The saturation was limited only by the colour gamut available on a CRT monitor at a reasonable luminance (20 cdm -2 ), which was five times that used by Michimata et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…The CRT monitor was the only source of light in an otherwise dark room. Rod intrusion cannot be ruled out with these screen luminances, however, Shepherd (1994) and Shepherd and Wyatt (2008) have previously used similar screen colours with luminances ranging from 58 cdm -2 to 2.5 cdm -2 and found, in a colour matching task, rod intrusion to become apparent only below 4.5 to 7.0 cd m -2 . This is returned to in the Discussion.…”
Section: Local and Global Displaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of rod hue biases have not revealed additional neural pathways for rod influence on blue/yellow hue appearance. However, some studies of chromatic discrimination have suggested there may be differences in rod influence on S-on and S-off pathways [40,41].…”
Section: Discussionmentioning
confidence: 99%